A novel approach for an immunogen against Corynebacterium pseudotuberculosis infection: An Escherichia coli bacterin expressing phospholipase D. (February 2021) - Barros de Pinho, Rodrigo; de Oliveira Silva, Mara Thais; Brenner, Gabriel; Dié Alves, Mirna Samara; Azevedo, Vasco; Dias Portela, Ricardo; Borsuk, Sibele
Abstract: Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis (CLA) in small ruminants. There is still needed an immunoprophylaxis model, which induces a protective and sustained immune response against the bacteria. In this study, we evaluated a recombinant Escherichia coli bacterin expressing the recombinant phospholipase D (rPLD) protein, the most relevant virulence factor of C. pseudotuberculosis, as a potential vaccine formulation. E. coli BL21 (DE3) Star strain was used for rPLD protein expression and was then inactivated by formaldehyde. Four groups with 10 Balb/c mice each were immunized twice within a 21 days interval: G1-control - 0.9% saline solution; G2- E. coli bacterin/pAE (naked plasmid); G3- E. coli bacterin/pAE/ pld ; G4-purified recombinant rPLD. Subsequently, the animals were challenged with a C. pseudotuberculosis virulent strain and evaluated for 40 days. The highest survival rate was observed for G3 with 40% protection, followed by 30% in the purified rPLD group (G4). These two groups also showed considerable IgG production when compared with the control group (G1). Also, a higher significant expression of interferon-γ was observed for the experimental groups G2, G3, and G4 when compared with a control group (G1) ( p  < 0.05). These results represent that a recombinant bacterin can be seen as a promising approach for vaccinal antigens against CLA, being possible to be used in association of different vaccine strategies. Graphical abstract: Image 1 Highlights: The E. coli bacterin expressing rPLD demonstrated its potential as an immunogen. This strategy is set apart by a significant reduction in vaccine production costs. Recombinant PLD bacterin is stable, non-toxic, and induce high levels of IFN-γ.